Polytopic cation receptor functional phthalocyanines: Synthesis, characterization, electrochemistry and metal ion binding - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Our efforts toward the development of the synthesis of a novel type of receptor ligand and its tetrasubstituted phthalocyanines, 2,9,16,23-tetrakis(6-hydroxyhexylsulfanyl) phthalocyanine, M[Pc(S-C6H13OH)(4)] (M = Zn(II), Cu(II), Co(II)), bearing sulfur and oxygen donor atoms on the periphery together with hexyl moieties, have been carried out together with spectroscopic and electrochemical characterization. The newly synthesized functional phthalocyanines were soluble in MeOH, EtOH, THF, DMF, CNP (alpha-chloronapthalene), DMSO and quinoline, and less soluble in i-PrOH and CH3CN. Cation binding abilities of the functional phthalocyanines with Ag+, Pd2+, Hg2+ and Cd2+, resulting in the formation of polynuclear phthalocyanine complexes, were evaluated by UV-Vis spectroscopic techniques. The spectroscopic properties of the complexes were affected strongly by the electron-donating sulfanyl units on the periphery. The cyclic voltammetry of the complexes were examined on a platinum electrode in DMSO. The new synthesized compounds have been characterized by elemental analysis, FTIR, H-1 and C-13 NMR, MS (ESI and MALDI-TOF) and UV-Vis spectral data. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanines; zinc; copper; cobalt; metal sensor; ionophore; aggregation; electrochemistry; GAS-SENSING PROPERTIES; ENERGY-TRANSFER; PORPHYRAZINES; REACTIVITY; COMPLEXES; LIGAND